The Evaluation of The Work of Ahmed Şem’i’s “Hülasatü’l Ahlak” with The Perception of The Moral Education of Our Age - Seval Yinilmez Akagündüz; Ahmet Doğan (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The work entitled “Hülâsatü’l-Ahlâk” penned by Ahmed Şem’i in 1907 is among the prominent works shedding light on the conception of education in the period of Abdulhamid II. It is well-known that significant steps were taken in every grade of education in that period. Some of those steps were newly founded schools, textbooks, and the attempt to introduce new methods into the education community. In this paper, the work entitled “Hülâsatü’l-Ahlâk” taught for moral education in rushdiyyas (state secondary school) in the era of Abdulhamid II is analyzed. The work in question is precious as it explains a lot about that period’s approach towards moral education. Ahmed Şem’i pointed out that he authored that work for the rushdiyya students since other moral books had prepared for idâdi (high school) and âli (college) students. In this regard, the work called “Hülâsatü’l-Ahlâk” has a substantial value in giving information about the education conception in the rushdiyyas in the era of Abdulhamid II and elucidating how the moral education of children should be. Document analysis was used in the study of the work of “Hülasatü’l-Ahlak”. No sample was used, and the entire work was examined by content analysis method. Based on the categories of “Good Values” and “Bad Values” and their sub-themes, it was found that the work included good values more than bad ones as a result of the calculation of frequency and percentage values.